Impact of Paprika (Capsicum annuum) Addition on Quality of Value-Added Goat Meat Spread - Raziuddin, M.; Babu, R. N.; Rao, V. Appa; Ramesh, S.; Karunakaran, R. (International Journal of Livestock Research, 2020)
Natural colorants seem to be an acceptable alternative to replace nitrite in improving the color of processed meat products. Value added processed meat products are prepared according to the demands of health-conscious consumers by using natural, organic, preservative free and easily available non meat ingredients in the marketplace. The present study was undertaken to evaluate the instrumental color, physico-chemical properties and sensory qualities of spent goat meat spread incorporated with different levels of paprika powder viz., control, 0.5%, 1.0% and 1.5%. Addition of paprika significantly increased the values of instrumental colour in value added goat meat spread. Instrumental color values of paprika incorporated value-added goat meat spread showed higher red coloration as compared to control. Incorporation of paprika in value added goat meat spread was ranked significantly higher for color and overall acceptability of product. Further, the values of pH, cooking yield and spreadability of paprika incorporated value-added goat meat spread were effect non-significant. Instrumental color, physico-chemical and sensory quality of value-added goat meat spread were enhanced by the addition of paprika.